A Review of Properties of Nanocellulose, Its Synthesis, and Potential in Biomedical Applications - Aayushi Randhawa; Sayan Deb Dutta; Keya Ganguly; Tejal V. Patil; Dinesh K. Patel; Ki-Taek Lim (Applied Sciences, 2022)
Cellulose is the most venerable and essential natural polymer on the planet and is drawing greater attention in the form of nanocellulose, considered an innovative and influential material in the biomedical field. Because of its exceptional physicochemical characteristics, biodegradability, biocompatibility, and high mechanical strength, nanocellulose attracts considerable scientific attention. Plants, algae, and microorganisms are some of the familiar sources of nanocellulose and are usually grouped as cellulose nanocrystal (CNC), cellulose nanofibril (CNF), and bacterial nanocellulose (BNC). The current review briefly highlights nanocellulose classification and its attractive properties. Further functionalization or chemical modifications enhance the effectiveness and biodegradability of nanocellulose. Nanocellulose-based composites, printing methods, and their potential applications in the biomedical field have also been introduced herein. Finally, the study is summarized with future prospects and challenges associated with the nanocellulose-based materials to promote studies resolving the current issues related to nanocellulose for tissue engineering applications.